(untitled) (Research, Society and Development, 2021)
Microemulsion is a thermodynamically stable dispersion consisting of an aqueous and an organic phases, both stabilized by surfactant molecules and when in need, co-active surfactant. The nature and structure of these components are essential in the formulation of microemulsified systems. For this, the construction of phase diagrams can be a fundamental tool to characterize the ideal experimental conditions for the existence and operation of microemulsions. Thus, the present work had as objective to obtain a comparison between microemulsions with different compositions through the construction of ternary diagrams, aiming to achieve the most stable system. To produce microemulsified systems, a non-ionic surfactant (Ultranex NP 60), a co-surfactant (Isopropyl Alcohol), two organic phases (pine oil and castor oil) and an aqueous phase (glycerin solution) were used. Also complementing the study, rheological tests of the oleic phases were accomplished, as well as their thermogravimetric analysis. The focus of the reached ternary diagrams was to find the system with the largest Winsor type IV region (microemulsion). It was verified this region had a significant increase by the addition of the co-surfactant in the medium and using a vegetable oil, such as pine oil, since it promotes strong surfactant-oil interactions on the interface.